The VE-PTP Inhibitor AKB-9778 Improves Antitumor Activity and Diminishes the Toxicity of Interleukin 2 (IL-2) Administration. Issue 7 (September 2019) - Li, Guanqiao; Sachdev, Ulka; Peters, Kevin; Liang, Xiaoyan; Lotze, Michael T.
Abstract : Administration of interleukin (IL)-2 has led to a durable response in patients with advanced renal cancer and melanoma but is restricted for clinical application because of adverse effects, including the vascular leak syndrome (VLS). VLS is associated with increased circulating levels of the Tie2 antagonist ligand, angiopoietin 2, and decreased Tie2 receptor phosphorylation and downstream signaling in endothelial cells (ECs). Given that vascular endothelial protein tyrosine phosphatase (VE-PTP) is a specific membrane phosphatase in ECs that dephosphorylates Tie2, the effects of targeting VE-PTP by a selective inhibitor AKB-9778 (AKB) in terms of VLS and antitumor efficacy were examined in this study. The authors found, by targeting VE-PTP, that the antitumor effects induced by IL-2 were augmented [tumor-free 44% (IL-2 alone) vs. 87.5% (IL-2+AKB)], associated with enhanced immune cell infiltrate (90% increase for CD8 T cells and natural killer cells). In addition, the side effects of IL-2 therapy were lessened, as demonstrated by diminished lung weight (less vascular leakage) as well as reduced cytokine levels (serum HMGB1 from 137.04±2.69 to 43.86±3.65 pg/mL; interferon-γ from 590.52±90.52 to 31.37±1.14 pg/mL). The authors further sought to determine the potential mechanism of the action of AKB-9778. The findings suggest that AKB-9778 may function through reducing serum angiopoietin 2 level and regulating EC viability. These findings provide insights into the targeting VE-PTP to improve tolerance and efficacy of IL-2 therapy and highlight the clinical potential of AKB-9778 for treating patients with VLS and cancer. Abstract : Supplemental Digital Content is available in the text.